Implementasi Pembelajaran Matematika Untuk Anak Berkebutuhan Khusus Tunagrahita Pada Siswa Sekolah Luar Biasa (SLB) Negeri 1 Mataram - Ahmad Badawi; Arjudin Arjudin; Ulfa Lu’luilmaknun; Amrullah Amrullah (Griya Journal of Mathematics Education and Application, 2022)
Implementation of Mathematics Learning for Children with Special Needs at special school (SLB) Negeri 1 Mataram Academic Year 2021/2022. The subjects of this research are teachers and students of VIII grade of Tunagrahita at Children with Special Needs at special school (SLB) Negeri 1 Mataram. The two chosen subjects are the class teacher and the randomly chosen student. This research is a Descriptive qualitative research. The data were collected in three phases, which are observation, interview and documentary. The result of this research shows the learning process for Children with Special Needs at special school (SLB) needs special treats and patterns for each student, even in fact the teachers still use the conventional method to teach them. The students still need guidance every hour. The teachers use more than one method as in other schools. The mathematics learning process of Children with Special Needs at special school (SLB) is little bit different to public schools where the teachers here have to be really slow when explaining the materials to the students and the teachers need to repeat more than twice in order that students understand it well. This Children with Special Needs school (SLB) uses the same evaluation as public schools use.